2013
DOI: 10.5511/plantbiotechnology.12.1210a
|View full text |Cite
|
Sign up to set email alerts
|

Rice monoculm mutation moc2, which inhibits outgrowth of the second tillers, is ascribed to lack of a fructose-1,6-bisphosphatase

Abstract: We characterized a rice monoculm mutant moc2, which showed significantly reduced tiller numbers, pale-green leaves, a reduced growth rate, and a consequent dwarf phenotype. The monoculm feature was attributed to a deficiency in the efficient outgrowth of tiller buds, although the moc2 mutant produced tiller buds. Inconsistent change was observed in the expression of genes involved in tiller bud outgrowth, suggesting that the moc2 mutant has a defective function necessary for the tiller bud outgrowth. The gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 33 publications
4
44
0
1
Order By: Relevance
“…A rice tiller occurs in a two-stage process: the formation of an axillary bud at each leaf axil and its subsequent outgrowth (Li et al, 2003;Li, 2008, 2011). To understand the molecular mechanisms underlying tiller bud formation, a number of mutants, such as monoculm 1 (moc1), monoculm 2 (moc2), lax panicle 1 (lax1) and lax2, have been isolated and characterized (Li et al, 2003;Oikawa and Kyozuka, 2009;Tabuchi et al, 2011;Koumoto et al, 2013). Among them, MOC1 is the first cloned gene that plays a key role in both the initiation and outgrowth of a tiller bud in monocot plants (Li et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A rice tiller occurs in a two-stage process: the formation of an axillary bud at each leaf axil and its subsequent outgrowth (Li et al, 2003;Li, 2008, 2011). To understand the molecular mechanisms underlying tiller bud formation, a number of mutants, such as monoculm 1 (moc1), monoculm 2 (moc2), lax panicle 1 (lax1) and lax2, have been isolated and characterized (Li et al, 2003;Oikawa and Kyozuka, 2009;Tabuchi et al, 2011;Koumoto et al, 2013). Among them, MOC1 is the first cloned gene that plays a key role in both the initiation and outgrowth of a tiller bud in monocot plants (Li et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The researchers speculated that the growth of tiller buds was inhibited or the tiller buds failed to enlarge to generate individual organ. Additionally, the researchers found that under high-temperature condition, the moc2 mutant sometimes could produce one tiller [6]. In this study, 80% of the ts1 plants kept monoculm or produced one tiller and the other 20% of them could produce only two tillers at tillering peak stage (40DAS).…”
Section: Discussionmentioning
confidence: 75%
“…Among them, MOC1 , a member of the GRAS family in rice, controls the formation of axillary buds and promotes their growth [5]. MOC2 , encodes cytosolic fructose-1, 6-bisphosphatase 1 (FBP1), is essential for the outgrowth of tiller buds in rice [6]. MOC3 , in which a point mutation causes the premature termination of OsWUS , is required for the formation of axillary buds of rice [7].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we need to balance tiller number and panicle size in breeding programs. There are 213 QTLs for tiller number in the Gramene database, and some genes controlling tiller number were cloned, such as the monoculm genes MOC1 (LOC_Os06g40780), MOC2 (LOC_Os01g64660), MOC3, (LOC_Os04g56780), and OsTB1 (LOC_Os03g49880) (Li et al 2003, Yao et al 2007, Koumoto et al 2013, Lu et al 2015. We identified only one QTL for number of effective tillers in this study.…”
Section: Discussionmentioning
confidence: 87%